Promenades poétiques et daguerriennes—Bellevue : Photography and Narration - Margaret Fields Denton (Interfaces)
Louis-Auguste Martin's Promenades poétiques et daguerriennes--Bellevue, a brochure length work that was published in 1850, was regarded at the time as the first publication in France to combine text with photographs. Martin was both author of the poem, which recounts a weekend trip to a village near Paris, and maker of the seven paper photographs inserted between the lines of the poem. His choice of title points to his intention to situate his work within the literary tradition of the Promenade. However, Bellevue is not only a promenade poétique, but also a promenade daguerrienne which signals that the images are not mere illustrations but participants in the narration of the Promenade. This essay argues that while adheres in many ways to the conventions of the Promenade, the insertion of photographs problematizes a key element of the genre, which is the tension between the immediacy of impressions as they are experienced during the activity of travel or walking, and the subsequent composition of these impressions.